Genomic Signature of Mismatch Repair Deficiency in Areca Nut–Related Oral Cancer. (October 2020) - Yang, W.F.; Qin, N.; Song, X.; Jiang, C.; Li, T.; Ji, P.; Li, Y.; Ding, D.; Wang, C.; Dai, J.; Jin, G.; Chen, T.W.; et al.
Areca nut (AN) chewing contributes to an increase of oral squamous cell carcinoma (OSCC) cases in South and Southeast Asia; however, genomic events underlying the carcinogenesis process of AN-related OSCC remain unclear. Here, we comprehensively describe the genomic and transcriptome alterations of 113 Chinese OSCC patients (89 AN related and 24 AN negative) by whole-exome sequencing and RNA sequencing, and we compared the genomic differences between AN-related and AN-negative samples by integrating sequencing data of 325 OSCC patients from The Cancer Genome Atlas database and 50 from a published Taiwanese study. We identified 11 significantly mutated genes for OSCC, including 4 novel ones ( ATG2A, WEE1, DST, and TSC2 ), of which WEE1 and ATG2A mutated with significantly higher rates in AN-related samples ( P = 0.04 and P = 0.003, respectively). Mutational signature analysis revealed that AN-related OSCCs were specially characterized by the genomic signature of mismatch repair deficiency (dMMR), which could also predict the prognosis status of AN-related OSCC. In addition, an elevated PD-L1 expression was also observed in both AN-related patients ( P = 3.71 × 10 −11 ) and those with a high dMMR level ( P = 1.99 × 10 −4 ). Further differential expression analysis and in vitro experiments confirmed the role of dMMR in the development of OSCC induced by AN exposure. Taken together, this study first revealed the molecular profiles and highlighted the role of dMMR in AN-related OSCC among the Chinese population and identified that AN-related OSCC may represent a potential cohort for effective anti-PD-1/L1 immunotherapy.